P04.78 Ultrarapid FGFR3 immunostaining for diagnosis of gliomas harboring FGFR3 gene fusions. (19th September 2018) - Mäntylä, S; Haapasalo, J; Ilvesaro, J; Nordfors, K; Isola, J; Haapasalo, H; Nykter, M; Granberg, K
Abstract: Background: Fibroblast growth factor receptor 3 (FGFR3) gene fusion with transforming acidic coiled coil 3 (TACC3) has been detected in a subset of diffuse gliomas and other malignancies. Tumors with FGFR3:TACC3 fusion are typically aggressive isocitrate dehydrogenase (IDH) wild-type tumors and are more commonly observed in female patients. Strong FGFR3 staining has been shown to be an indicator of FGFR3 fusions and is also associated with worse survival of patients. Different FGFR inhibitors are currently being clinically tested for various cancer types harboring FGFR alterations, and tumors with FGFR3 fusions have shown promising treatment responses. Intraoperative screening of FGFR3 fusion in gliomas could be beneficial due to the possibility of therapeutic FGFR inhibition. High to moderate FGFR3 staining is a prognostic marker and could be thus informative when the extent of the resection is considered. Intraoperative FGFR3 staining could also enable the targeted administration of FGFR-inhibitors into the tumor cavity. Therefore, we aimed to investigate whether a rapid immunohistochemical staining could be used intraoperatively to predict FGFR3 fusion status of tumors on frozen tissue sections. Material and Methods: Ultrarapid FGFR3 immunohistochemical staining was performed on frozen tissue sections from 34 astrocytomas (grades II-IV), five oligodendrogliomas (grades II-III) and two ependymomas (grades II and III). Results were histologically graded and cases with moderate to strong FGFR3 staining were selected for further analysis. Results: Staining protocol was simple and practical to carry out. The protocol can be performed in under ten minutes, which makes it suitable for the use in intraoperative setting. Conclusion: Ultrarapid-FGFR3 immunostaining would be beneficial for the diagnosis of FGFR3 fusion positive gliomas and other malignancies when carried out intraoperatively, since it is quick to perform and it nicely separates tissues with moderate to high staining. Intraoperatively this protocol could provide valuable information on the extent of the resection required to achieve the best treatment outcome in combination with targeted inhibitory treatment.